Constructive Discipline Consequences and Fifth-Graders' Learning Motivation at SDN 1 Selebung Ketangga - Moh. Irwan Hadi (PALAPA, 2023)
Classroom discipline should be understood not merely as behavioral control but as an educational consequence that guides students toward responsible learning behavior. This study aims to examine the relationship between constructive discipline consequences and the learning motivation of fifth-grade students at SDN 1 Selebung Ketangga in the 2022/2023 academic year. A quantitative approach with an ex post facto design was employed. The sample comprised all fifth-grade students in the classroom under study, selected through total sampling. Data were collected through questionnaires, observation, and documentation and analyzed using simple linear regression with SPSS 22. The findings show that constructive discipline consequences, operationalized through educational punishment, have a positive and significant effect on students’ learning motivation, as indicated by a regression coefficient of 2.974 and a significance value of 0.006 (< 0.05). The R Square value of 1.000 indicates an extremely high predictive level in the available dataset; therefore, the model should be interpreted with caution in the context of educational behavioral research. These findings suggest that proportional, nonphysical, non-humiliating, and pedagogically explained discipline consequences can serve as behavioral feedback that supports students’ learning engagement. This study concludes that constructive discipline contributes to learning motivation when implemented ethically and educationally. Theoretically, this study contributes to classroom management research by reframing discipline as a pedagogical strategy rather than a punitive mechanism. Practically, it highlights the importance of discipline practices that protect students’ dignity, strengthen positive learning habits, and support responsible classroom behavior.